Factors Influencing the Improved Market Standing of Insurance Companies - Grzebieniak, Andrzej (Olsztyn Economic Journal, 2014)
The aim of this article is to identify factors influencing the improvement of the market standing of insurance companies. The following hypothesis was taken into consideration in this elaboration - the market standing of an insurance company is shaped not only by the quality and price of products, but also by the quality of consumer service as well as the company’s good name. The identification of the factors was done on the basis of a self-based study in which survey research was used and the data collection instrument was a self-completed questionnaire. The survey was sent by post or via the Internet to all 63 insurance companies located and run in Poland between 2008-2010. 57 questionnaires were correctly completed and sent back.